The Barnstone studios - Barnstone, Myron; The Barnstone Studios (Estados Unidos); 3Seed Marketing & Design Studio (Estados Unidos) (USA : The Barnstone Studios, 2014)
Está "Serie completa de Video" y el legendario instructor de arte Myron Barnstone, da técnicas de dibujo y diseño. Proporciona las herramientas que necesita para dominar el dibujo y el diseño de figuras.
Introduction to drawing systems: (Disc 1. Lesson 1. Introduction to drawing systems : the two-dimensional elevation ; Lesson 2. The two-dimensional still life arrangement--Disc 2. Lesson 3. The construction and truncation of a sphere ; Lesson 4. The construction of three-dimensional forms--Disc 3. Lesson 5. The sphere in value ; Lesson 6. The value zone system applied to a still life--Disc 4. Lesson 7. Introduction to the root two rectangle ; Lesson 8. The plant assignment--Disc 5. Lesson 9. The portrait ; the geometry of the human head ; Lesson 10. An overview of dynamic symmetry : the rectangles--Drawing 1 Extra (CD)--Palette control & color theory: (Disc 1. Lesson 1--Disc 2. Lessons 2 & 3--Disc 3. Lessons 4 & 5--Disc 4. Lessons 6 & 7-- Homeworkg assignments and handouts (CD)--Introduction to figure drawing--Golden section-Unclocking the secrets of design
Los 11 videodiscos y 2 discos compactos en un envase
Keywords: DIBUJO -- ESTUDIO Y ENSEÑANZA; DIBUJO -- TECNICAS; DIBUJO -- METODOS; COLOR -- ESTUDIO Y ENSEÑANZA